Judges 1:1–36: The Deuteronomistic Reintroduction of the Book of Judges - Mullen, E. Theodore (Harvard theological review, 1984)
In its present position within the literary structure of the Book of Judges, Judg 1:1–2:5 stands as an introduction to those events purported to have transpired following the death of Joshua (1:1a). When it is read within the context of the deuteronomistic history as a whole, however, it is apparent that such cannot be the case, since most of the narrated events in Judg 1:3–36 have already been reported in Joshua 14–19. Thus, the present introduction to the Book of Judges appears to be a secondary and somewhat awkward redactional gloss to the deuteronomic account of the era of the Judges in the period after the initial entry into the land recounted in Joshua 2–12. The separation of Judg 1:1–2:5 is based on the investigations of the literary compilation of the predeuteronomic stories of the “deliverers” and the recognition that Judg 2:6–3:6 serves as the original deuteronomic introduction to this period of Israel's history. But despite the assertions of its secondary literary nature and its numerous parallels with Joshua 14–19, Judg 1:1–36 is generally seen as a collection of miscellaneous fragments of varying dates and varying reliability which presents a partial description of the initial occupation of the land. Judg 1:1–36 stands in distinct contrast to the pan-Israelite view presented in Joshua 2–12 and is thus of historical importance for a reconstruction of the period of the settlement. In general, modern scholarship has separated the introductory section of the Book of Judges from the body of the work it serves to inaugurate in its canonical form and has insisted that this introduction has no immediate or contextual connections with the stories that follow it.